Water masses distribution in the Southern Ocean: improvement of an extended OMP (eOMP) analysis - Pardo, PC; Perez, FF; Velo, A; Gilcoto, M (2012)
The Southern Ocean (SO) is a major part of the global ocean circulation. The formation and mixing of water masses in the SO cause changes in the northward flow of the Meridional Overturning Circulation and as a consequence, in the Earth’s climate. There have been numerous studies of the SO but a full understanding is difficult to achieve due to the complexity of the processes of formation and mixing of the different water masses. This work aims to clarify some of these aspects through an extended Optimum Multiparametric analysis, using data downloaded from the GLODAP and CARINA databases. A total of 11 source water masses were selected accurately describe the physical and biochemical properties of the SO. Shelf surface waters were included in order to accommodate the complex shelf processes involved in the formation of Antarctic bottom Waters. The methodology here developed takes into account the remineralisation of organic matter and as an improvement; the variability of data related to the processes of dissolution of CaCO 3 and opal. The results from this analysis are accurate and reliable and led to very informative conclusions. Thus, a volumetric census is presented, which confirms Circumpolar Deep Water (CDW; 53 ± 3% of the SO volume) as the most volumetrically important water mass in the SO; followed by Antarctic Bottom Water (AABW; 17 ± 0.9%) and North Atlantic Deep Water (NADW; 13 ± 0.8%). AABW properties are the result of the predefined combination of its three major types, i.e., 77% Weddell Sea Bottom Water, 20% Ross Sea Bottom Water and 3% Adélie Bottom Water. CDW comprises 65% AABW, 30% NADW and 5% Antarctic Intermediate Water, according to the relationship between their conservative properties (potential temperature and salinity). Therefore, the volume occupied by AABW and NADW in the SO rises to 51 ± 2% and 28 ± 0.8%, respectively. The ratio between AABW and NADW is 1.79 ± 0.03, which is inside the expected range of 1–3. Considering the Atlantic sector of the SO (70°W–80°E), which is the more ...